UPACARA BATAGAK PANGULU DALAM SUKU KAMPAI NAGARI BALIMBING KECAMATAN RAMBATAN KABUPATEN TANAH DATAR - Restu Fauzi; Prof. Dr. Isjoni, M.Si '; Drs. Tugiman, MS ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is 1) to find out the historical appointment ceremony of pangulu at Balimbing village of Rambatan subdistrict of Tanah Datar regency 2) to know the proces appointment ceremony of pangulu on Kampai clan at Balimbing village of Rambatan subdistrict of Tanah Datar regency 3) to find out how important meaning appointment ceremony of pangulu for the society of Balimbing village of Rambatan subdistrict of Tanah Datar regency 4) to see implicit values on appointment ceremony of pangulu at Balimbing village of Rambatan subdistrict of Tanah Datar regency. This research is used qualitative method which is giving the complete information that will useful for knowledge. The result of this research shows the society of Balimbing village of Rambatan subdistrict of Tanah Datar regency hold appointment ceremony of pangulu with multiple processes that has a very important meaning for the society in bequeath cultural values and continuing traditional leadership on Kampai clan of Balimbing villageKey Words : Appointment ceremony of pangulu Kampai Clan